The Role of Islamic Religious ‎Education in Maintaining Adolescent ‎Moral Values ‎ - Fahmi Hanifa; Zaiyad Zubaidi (CV Naskah Aceh, 2026)
This research is motivated by the problem of moral decline recently affecting several generations of teenagers. Symptoms of moral decline include the spread of cases of drug abuse, promiscuity, crime, violence, and other less than commendable behavior. Even the behavior of acts of violence lately is so viral and has become a concern, which is carried out by teenagers. The purpose of this study was to determine the role of Islamic religious education teachers in building student character. This study used descriptive qualitative research, while data collection techniques were carried out through a literature review. The results of this study indicate that the supporting and inhibiting factors of Islamic religious education teachers in fostering student character, namely in terms of supporting factors are the family environment and conducive school environment and the existence of communication between teachers and parents of students while the inhibiting factors usually occur due to the lack of awareness of students about the importance of character values ​​and the environmental conditions in which students live and also their peers in society.